Energy and power fluctuations in ac-driven coherent conductors - Battista, Francesca (2014)
Using a scattering matrix approach we study transport in coherent conductors driven by a timeperiodic bias voltage. We investigate the role of electron-like and hole-like excitations created by the driving in the energy current noise and we reconcile previous studies on charge current noise in this kind of systems. The energy noise reveals additional features due to electron-hole correlations. These features should be observable in power fluctuations. In particular, we show results for the case of a harmonic and bi-harmonic driving and of Lorentzian pulses applied to a two-terminal conductor, addressing the recent experiments of Refs. 1 and 2.